New Heterocyclic Systems for New Pharmaceuticals - Bogza, S.L. (Science and Innovation, 2024)
The researches in the field of heterocyclic and medicinal chemistry carried out by the Department of Biologically Active Compounds of the Litvinenko Institute of Physical Organic and Coal Chemistry of the NAS of Ukraine have been reviewed. The results of search of new pharmaceuticals with basic β-carboline structures, its S- and O- isosteres, and isoquinoline have been showed.